The mathematics of money : - Biehler, Timothy J. (McGraw-Hill/Irwin, 2008)
The Mathematics of Money: Math for Business and Personal Finance covers all the traditional topics of the business math course, but with a more algebraic focus than many of the texts currently on the market. The text develops a solid understanding of percent and interest early, then applies that foundation to other applications in business and personal finance. While it is appropriate for students of all levels, the book takes the approach that even if students are coming into the class with only high school math, neither they nor the instructor need to be afraid of algebra; it takes care to clearly present and reinforce the formulas given and to consistently return to them and apply the material to contexts that are relevant to the students.